OsBSK2, a putative brassinosteroid-signalling kinase, positively controls grain size in rice. (20th May 2022) - Yuan, Hua; Xu, Zhengyan; Chen, Weilan; Deng, Chaoyang; Liu, Yi; Yuan, Min; Gao, Peng; Shi, Hui; Tu, Bin; Li, Ting; Kang, Liangzhu; Ma, Bingtian; et al.
Abstract : OsBSK2, a putative BR signalling kinase, directly interacts with the BR receptor kinase OsBRI1, and controls grain size independent of the BR signalling pathway. Abstract: Grain size is an important trait that directly affects grain yield in rice; however, the genetic and molecular mechanisms regulating grain size remain unclear. In this study, we identified a mutant, grain length and grain weight 10 ( glw10 ), which exhibited significantly reduced grain length and grain weight. Histological analysis demonstrated that GLW10 affects cell expansion, which regulates grain size. MutMap-based gene mapping and transgenic experiments demonstrated that GLW10 encodes a putative brassinosteroid (BR) signalling kinase, OsBSK2. OsBSK2 is a plasma membrane protein, and an N-myristoylation site is needed for both membrane localization and function. OsBSK2 directly interacts with the BR receptor kinase OsBRI1; however, genetic experiments have demonstrated that OsBSK2 may regulate grain size independent of the BR signalling pathway. OsBSK2 can form a homodimer or heterodimer with OsBSK3 and OsBSK4, and silencing OsBSK2, OsBSK3, and OsBSK4 reduce grain size. This indicates that OsBSKs seem to function as homodimers or heterodimers to positively regulate grain size in rice. OsBSK2/3/4 are all highly expressed in young panicles and spikelet hulls, suggesting that they control grain size. In summary, our results provide novel insights into the function of BSKs in rice, and identify novel targets for improving grain size during crop breeding.